Establishing Worksite Wellness Programs for North Carolina Government Employees, 2008 - Suzanna Young, MPH; Jacquie Halladay, MD, MPH; Marcus Plescia, MD, MPH; Casey Herget, MSW, MPH; Carolyn Dunn, PhD (Centers for Disease Control and Prevention, 2011)
BackgroundState employee health plans sometimes provide worksite wellness programs to reduce the prevalence of chronic diseases among their members, but few offer the comprehensive range of interventions recommended by the Task Force on Community Preventive Services.Community ContextNorth Carolina's State Health Plan for Teachers and State Employees provides health coverage for approximately 665,000 state employees, teachers, retirees, and dependents. Health claims indicate that the prevalence of having at least 1 chronic disease or of being obese is approximately 32% among state employees.MethodsThe State Health Plan created a partnership with North Carolina's Division of Public Health, Office of State Personnel, and other key state agencies to identify bureaucratic obstacles to providing worksite wellness programs for state employees and to develop a state policy to address them. The Division of Public Health established a model worksite program to guide development of the worksite wellness policy and pilot wellness interventions.OutcomeThe state's first worksite wellness policy created an employee wellness infrastructure in state government and addressed administrative barriers to allow effective worksite wellness interventions. For example, the policy led to pilot implementation of a subsidized worksite weight management program. Positive results of the program helped generate legislative support to expand the weight management program throughout state government.InterpretationStrong interagency partnership is essential to guide worksite wellness policy and program development in state government. State health plans, public health agencies, and personnel agencies each play a role in that partnership.